Diffuse continental deformation: length scales, rates and metamorphic evolution. - England, P (1987)
Large-scale continental deformation may be treated as a quasi-continuous process, and the object of this paper is to outline controls on the length scales and rates of deformation of such a continuous lithosphere, and to relate them to the thermal and mechanical evolution of large compressional belts. The dependence of deformation on convergent boundary length implies that for fixed velocity of convergence, strain rates decrease with increasing length of the orogen. From experimental work, the scale length of compressional deformation decreases as the fraction of the lithospheric strength supported by friction on faults, increases. This fraction depends on the thermal profile of the continental lithosphere and on evolution of the orogenic belt. The thermal development of a diffusely deforming compressional belt is nearly independent of its strain history unless the strain rates are < approx 10-15/s. If extension of the thickened crust ends metamorphism, peak metamorphic conditions depend only on the rheology of the lithosphere. Metamorphism so subject to extension following orogenesis should be nearly independent of the initial thermal conditions of the crust, and may be distinguished from metamorphism terminated by erosion by a final stage of isobaric cooling.(This and the following 12 abstracts represent papers presented in a Discussion Meeting on Tectonic settings of regional metamorphism, organized and edited by E.R. Oxburgh, B.W.D. Yardley and P.C. England.)-R.K.H.